Polymeric surfactants for enhanced oil recovery: A review of recent progress - Afolabi, F. (Elsevier B.V., 2022)
Chemical enhanced oil recovery (CEOR) is a well-recognized technique for exploiting the original oil in place (OOIP) left behind in subsurface petroleum reservoirs after primary and secondary recovery processes. However, CEOR is not practiced or implemented widely because of project cost, operational and technical complexity, and environmental risks. Polymeric surfactants have emerged as a viable alternative to conventional chemical methods. They offer multifunctional mechanisms such as viscosity increment and interfacial tension (IFT) reduction. Thus, they are thought to be more versatile in enhancing recovery due to mobility control and wettability-induced fluid redistribution. This review presents a summary of recent studies in the literature that provides new insights into the properties, mechanisms, and applications of polymeric surfactants related to improved hydrocarbon recovery. From the published studies, fluid-fluid interactions influencing rheology and IFT, and fluid-rock interactions dictating wettability alteration and adsorption tendencies, are systematically evaluated. Implications of these mechanisms on enhanced hydrocarbon recovery by the polymeric surfactants are analyzed. Recent advances and knowledge gaps are highlighted, and possible directions to improve research methodology are suggested. Â© 2021 Elsevier B.V.